2021
DOI: 10.1016/j.ebiom.2021.103338
|View full text |Cite
|
Sign up to set email alerts
|

Differential miRNAs in acute spontaneous coronary artery dissection: Pathophysiological insights from a potential biomarker

Abstract: Background Spontaneous Coronary Artery Dissection (SCAD) is an important cause of acute coronary syndromes, particularly in young to middle-aged women. Differentiating acute SCAD from coronary atherothrombosis remains a major clinical challenge. Methods A case-control study was used to explore the usefulness of circulating miRNAs to discriminate both clinical entities. The profile of miRNAs was evaluated using an unbiased human RT-PCR platform and confirmed using indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…There are studies demonstrated that the serum level of miR-146a-5p was elevated in patients with acute coronary syndrome (ACS) compared with healthy control subjects. 30 , 31 The spontaneous coronary artery dissection (SCAD), an important cause of ACS, caused a higher increase of miR-146a-5p than atherothrombotic acute myocardial infarction (AT-AMI) did. 31 Interestingly, the plasma level of MMP2 in SCAD patients was higher than that in AT-AMI, 31 suggesting a possible link between miR-146a-5p and MMP2 in SCAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies demonstrated that the serum level of miR-146a-5p was elevated in patients with acute coronary syndrome (ACS) compared with healthy control subjects. 30 , 31 The spontaneous coronary artery dissection (SCAD), an important cause of ACS, caused a higher increase of miR-146a-5p than atherothrombotic acute myocardial infarction (AT-AMI) did. 31 Interestingly, the plasma level of MMP2 in SCAD patients was higher than that in AT-AMI, 31 suggesting a possible link between miR-146a-5p and MMP2 in SCAD.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 The spontaneous coronary artery dissection (SCAD), an important cause of ACS, caused a higher increase of miR-146a-5p than atherothrombotic acute myocardial infarction (AT-AMI) did. 31 Interestingly, the plasma level of MMP2 in SCAD patients was higher than that in AT-AMI, 31 suggesting a possible link between miR-146a-5p and MMP2 in SCAD. Furthermore, the exposure to PM2.5 could also increase miR-146a-5p expression in ST elevated MI (STEMI) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many biological processes, such as cell proliferation, differentiation, and apoptosis, are reported to be regulated by miRNAs [ 16 ]. Thus, miRNAs are considered to play an important role in intercellular communication with relevant roles in various physiological and pathological processes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this article of EBioMedicine, Lozano-Prieto and colleagues report on the diagnostic power of circulating microRNAs for this purpose [4]. MicroRNAs are endogenous short non-coding RNAs with a major influence in the pathogenesis of cardiovascular diseases [5,6].…”
mentioning
confidence: 99%